2012
DOI: 10.1364/oe.20.020059
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal converting point of color temperature conversion complied with ANSI C78 377 for indoor solid-state lighting and display applications

Abstract: In recent years, displays and lighting require color temperature (CT) conversion function because observers have different preferences. This paper proposes effective methods to determine the optimal converting point of CT conversion for display and lighting application. For display application, the concepts of center of gravity and isotemperature line are applied to determine the optimal converting point. The maximal enhancement of luminance between the optimal and average is 18%. For lighting application, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Lastly, although Smet et al [12] and Walraven and Werner [31] confirmed that white perception is luminance invariant, more in-depth studies would be worthwhile to investigate the effect of luminance in combination with chromaticity. Otherwise, the maximal luminance could be obtained for a target chromaticity using the optimal converting point suggested by Hsieh et al [32]. Nonetheless, the present study builds upon and extends earlier studies, with increased insights that could act as good stepping stones for future deliberations on white perception.…”
Section: Discussionsupporting
confidence: 65%
“…Lastly, although Smet et al [12] and Walraven and Werner [31] confirmed that white perception is luminance invariant, more in-depth studies would be worthwhile to investigate the effect of luminance in combination with chromaticity. Otherwise, the maximal luminance could be obtained for a target chromaticity using the optimal converting point suggested by Hsieh et al [32]. Nonetheless, the present study builds upon and extends earlier studies, with increased insights that could act as good stepping stones for future deliberations on white perception.…”
Section: Discussionsupporting
confidence: 65%
“…The coordinate system is then transformed to the CIE 1976 color space because the chromaticity of this space is more uniform than the CIE 1931 color space [39].…”
Section: Photometric Theorymentioning
confidence: 99%
“…The isotemperature line that denotes the CCT of the luminaire is perpendicular to the Planckian locus and can be approximated with a high degree of certainty using the third-power polynomial shown below [39], [40].…”
Section: Photometric Theorymentioning
confidence: 99%